Inwentarz kościoła i plebanii w Kosowie w 1751 roku - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The inventory coming from the Diocesan Archive of Drohiczyn is the detailed records of the state of the church and presbytery drawn up by the dean Rev. Krzysztof Modzelewski on 19 January 1751. The inventory was drawn up due to the fact that the parish in Kosów was taken over by Rev. Benedykt Rumszewicz. The former Polish borderland parish is now located within the borders of Belarus.